ELL Corner - Linguistic Modifications in Action (Part 3 of 3) (pp. 1–18) - Norval, Brooke; Castaneda, Martha (Ohio Journal of School Mathematics, 2020)
The following is the third installment in a three-part series exploring ways to modify mathematics tasks to make them more equitable for English language learners (ELLs). In this third installment, the authors show explicit examples of how to linguistically modify mathematics test items.